EXPERIÊNCIA MÍSTICA EM “MISS ALGRAVE”, DE CLARICE LISPECTOR - Sacramento, Douglas Santana Ariston (Inventário, 2023)
Clarice Lispector (1920-1977) is a writer who figures in the canon of Brazilian national literature. Among her writings, which permeate some literary genres, her production with short stories stands out. “Miss Algrave” is one of those short stories that make up the collection A via crucis do corpo, and portrays the homonymous character, a woman who lives in an England full of restrictions and moralities of Christian dogma. Until, one Saturday night, she has a mystical experience marked by the erotic, with a being from Saturn, Ixtlan, who takes her virginity and transforms Miss Algrave’s life completely. Thus, this article undertakes a reading of the short story considering the ascesis experienced by the female character before the mystical experience and the mystical experience itself. Therefore, this discussion is based on theorists who discuss the relationship between literature and religious experience or who study Clarice’s work from a philosophical point of view.